Pathogenesis of Chronic Liver Injury and Hepatocellular Carcinoma in Alpha-1-Antitrypsin Deficiency - Perlmutter, David H (Pediatric research, 2006)
Alpha-1-antitrypsin (AT) deficiency is the most common genetic cause of liver disease in children. In addition to chronic liver inflammation and injury, it has a predilection to cause hepatocellular carcinoma later in life. The deficiency is caused by a mutant protein, ATZ, which is retained in the endoplasmic reticulum (ER) in a polymerized form rather than secreted into the blood in its monomeric form. The histologic hallmark of the disease is ATZ-containing globules in some, but not all, hepatocytes. Liver injury results from a gain-of-toxic function mechanism in which mutant ATZ retained in the ER initiates a series of pathologic events, but little is known about the mechanism by which this leads to carcinogenesis. Several recent observations from my laboratory have led to a novel hypothetical paradigm for carcinogenesis in AT deficiency in which globule-containing hepatocytes are "sick," relatively growth suppressed, but also elaborating trans-acting regenerative signals. These signals are received and transduced by globule-devoid hepatocytes, which, because they are younger and have a lesser load of accumulated ATZ, have a selective proliferative advantage. Chronic regeneration in the presence of tissue injury leads to adenomas and ultimately carcinomas. Aspects of this hypothetical paradigm may also explain the proclivity for hepatocarcinogenesis in other chronic liver diseases, including other genetic diseases, viral hepatitis, and nonalcoholic steatohepatitis.